Pitfalls of femoral Titanium Elastic Nailing. (June 2015) - Salonen, A.; Lahdes-Vasama, T.; Mattila, V. M.; Välipakka, J.; Pajulo, O.
Background and Aims: Despite several potential complications of elastic intramedullary nailing, it is currently the treatment of choice for femoral diaphyseal fractures in school-aged children. This study aimed to critically evaluate the complications of titanium elastic nailing in pediatric femoral shaft fractures. Material and Methods: This study evaluated patients with a diaphyseal femoral fracture treated with titanium elastic nailing (TEN) in Tampere University Hospital in Finland. The study group included 32 children with a mean age of 9 years during a 5-year period, from 1 January 2003 to 31 December 2007. Data were collected from medical records and x-rays. Mean follow-up time was 42 months. Results: Of 32 patients, 9 (28%) reported a postoperative complication. Complications were associated with nail prominence in five (16%) patients and instability in four (12%) patients. In patients with nail prominence, the titanium elastic nailing–nail ends were unbent and 10–35 mm outside the cortex of the distal femur. The nail prominence caused pain and delayed knee mobilization until the nail was removed after a mean time of 4 months. In patients with fracture instability, the mean titanium elastic nailing–nail/medullary canal diameter ratio was 46% and periosteal callus formation was 5.4 mm at the first control. In those with stable fractures, the values were 66% and 9.2 mm, respectively. Conclusions: Based on this study, two types of pitfalls in a small volume center were found. Titanium elastic nail ends were left unbent and too long. We recommend palpating the nail ends to exclude nail prominence and to verify free movement of the knee after nail cutting and bending. Fracture instability was caused by inserting titanium elastic nailing–nails that were too narrow. To avoid this complication, careful preoperative planning to select the proper-size titanium elastic nailing–nails and intraoperative testing of fracture stability under continuous fluoroscopy after the operation is advised.